Jihad dalam Perspektif K.H. Ahmad Sanusi (Kajian Analisis Ayat-Ayat Peperangan dalam Tafsir Tamsyiyyah Al-Muslimin fi Kalami Robbi Al-‘Alamin) - Umar Abdul Aziz; Subur Wijaya (LP2M Universitas PTIQ Jakarta, 2019)
This article describes the interpretation presented by K.H Ahmad Sanusi of several verses that explain about jihad (verses of war orders) in his commentary work Tamsyiyyah al-Muslimin fi Kalam Robbi al‘Alamin.The results of the study concluded that K.H Ahmad Sanusi interpreted verses about jihad as verses containing physical warfare orders with the aim of reviving or elevating the religion of Allah in a context limited to the time of war. K.H. Ahmad Sanusi lived during the two colonial periods, namely the Netherlands and Japan, which made his interpretation of jihad mean war against the Dutch and Japanese, because indeed at that time Indonesia was not yet independent and under Dutch occupation, which was continued with Japanese occupation. Although the interpretation of the verses of jihad does not include all verses in the Qur’an because of K.H. Ahmad Sanusi has not had time to finish his 30 Juz’ interpretation work, but his interpretation is still interesting as a study object, because the value of its locality that influences and contextualizes the time he lived. This is where, among others, differences in young interpretations with other masters.